Dampak Kebijakan Tata Tertib Sekolah Terhadap Perilaku Siswa - Rita Kurnia Murni; Muhamad Ali; Hary Murcahyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to explore the impact of school regulations on student discipline using a qualitative method with a case study approach. Data were collected through observations and interviews with students and teachers. The results indicate that school regulations play a central role in shaping student discipline, providing a framework for behavior and clear consequences. Teachers and student affairs staff play a significant role in enforcing rules with fair sanctions. Intracurricular and extracurricular activities help maintain order and provide positive experiences. However, the positive impact is also balanced with attention to negative effects, such as feelings of restraint. Students' awareness of rule consequences is acknowledged as a crucial element in shaping character and self-discipline, an essential perspective in preparing students for the future. In conclusion, the implementation of school regulations at MA NWDI Pancor has a central role in creating an effective learning environment and shaping positive student behavior. Keywords: Student Behavior, School Regulations.